2010
DOI: 10.3762/bjoc.6.108
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-(quinolin-2-yl)- and 3,6-bis(quinolin-2-yl)-9H-carbazoles

Abstract: SummaryA simple and efficient synthesis of novel 3-(quinolin-2-yl)- and 3,6-bis(quinolin-2-yl)-9H-carbazoles, utilizing sodium ethoxide as a catalyst via a Friedländer condensation reaction between 3-acetyl-9-ethyl-9H-carbazole or 3,6-diacetyl-9-ethyl-9H-carbazole and β-aminoaldehydes or β-aminoketones is described. All of the title compounds were obtained in good yields of 52–72% and their structures were confirmed by IR, 1H NMR, MS, and elemental analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Such compounds might be important for pharmacological studies or in the development of new medicinal products with interesting properties. Therefore, in continuation of our studies concerning the preparation of potential biologically active heterocyclic compounds [2730], we now report herein a facile and inexpensive procedure for the preparation of novel hybrid molecules, i.e., 2-(benzofuran-2-yl)-6,7-methylenedioxyquinoline-3-carboxylic acid derivatives ( 3 , Fig. 1) under mild conditions.…”
Section: Introductionmentioning
confidence: 96%
“…Such compounds might be important for pharmacological studies or in the development of new medicinal products with interesting properties. Therefore, in continuation of our studies concerning the preparation of potential biologically active heterocyclic compounds [2730], we now report herein a facile and inexpensive procedure for the preparation of novel hybrid molecules, i.e., 2-(benzofuran-2-yl)-6,7-methylenedioxyquinoline-3-carboxylic acid derivatives ( 3 , Fig. 1) under mild conditions.…”
Section: Introductionmentioning
confidence: 96%
“…However, we have not yet found any literature reported on their reaction with 8-hydroxylquinolines for construction of the bisquinoline skeleton. Thus, on the basis of our previous work [35][36][37][38], 2-chloromethylquinoline (4c) was first subjected to the Williamson reaction with 8-hydroxylquinoline (5a) in the presence of K 2 CO 3 in MeCN. It was found that the reaction proceeded well and the thin layer chromatography (TLC) analysis did not indicate the formation of any distinct byproduct.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18] Furthermore, carbazole derivatives are widely used as building blocks for new organic materials and play a very important role in electroactive and photoactive materials. [19] Currently, there is a strong interest in the synthesis of novel heteroarylcarbazole derivatives having their important structural features and promising biological activities. [20] Although most heteroarylcarbazoles reported in the literature contain a common heterocyclic ring moiety fused with a carbazole such as pyridocarbazoles, thienocarbazole, quino and chromecarbazoles, pyranocarbazoles, pyrrolo carbazoles, indolocarbazoles and their synthetic analogues, to the best of our knowledge, there are very few reports where the heteroaryl moiety is substituted with a carbazole unit.…”
Section: Introductionmentioning
confidence: 99%